Functional and prognostic significance of the genomic amplification of frizzled 6 (FZD6) in breast cancer - Corda, G; Sala, G; Lattanzio, R; Iezzi, M; Sallese, M; Fragassi, G; Lamolinara, A; Mirza, H; Barcaroli, D; Ermler, S; Silva, E; Yasaei, H; et al. (John Wiley & Sons Ltd, 2016)
Frizzled receptors mediate Wnt ligand signalling, which is crucially involved in regulating tissue development and differentiation, and is often deregulated in cancer. In this study, we found that the gene encoding the Wnt receptor frizzled 6 (FZD6) is frequently amplified in breast cancer, with an increased incidence in the triple-negative breast cancer (TNBC) subtype. Ablation of FZD6 expression in mammary cancer cell lines: (1) inhibited motility and invasion; (2) induced a more symmetrical shape of organoid three-dimensional cultures; and (3) inhibited bone and liver metastasis in vivo. Mechanistically, FZD6 signalling is required for the assembly of the fibronectin matrix, interfering with the organization of the actin cytoskeleton. Ectopic delivery of fibronectin in FZD6-depleted, triple-negative MDA-MB-231 cells rearranged the actin cytoskeleton and restored epidermal growth factor-mediated invasion. In patients with localized, lymph node-negative (early) breast cancer, positivity of tumour cells for FZD6 protein identified patients with reduced distant relapse-free survival. Multivariate analysis indicated an independent prognostic significance of FZD6 expression in TNBC tumours, predicting distant, but not local, relapse. We conclude that the FZD6-fibronectin actin axis identified in our study could be exploited for drug development in highly metastatic forms of breast cancer, such as TNBC. © 2016 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.